Comparison of characteristics and outcomes on ETP-ALL/LBL and non-ETP ALL patients receiving allogeneic hematopoietic stem cell transplantation - Chen, Juan; Liu, Li; Ma, Runzhi; Pang, Aiming; Yang, Donglin; Chen, Xin; Wei, Jialin; He, Yi; Zhang, Rongli; Zhai, Weihua; Ma, Qiaoling; Jiang, Erlie; et al. (Frontiers in Oncology, 2023)
Objective: To compare the characteristics of ETP-ALL/LBL (early T-cell precursor acute lymphoblastic leukemia/lymphoma) and non-ETP ALL patients and the outcomes of these patients after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Method: A total of 57 patients with T-cell acute lymphoblastic leukemia/lymphoma receiving allo-HSCT at our center between January 2016 and March 2022 were enrolled in the study. Twenty-eight patients were diagnosed as ETP-ALL/LBL (28/57, 49.12%) in the cohort. Results: The baseline characteristics was not significantly different between the two groups. The median time for myeloid engraftment was 14 days (range from 11 to 21) versus 14 days (range from 10 to 20) (P =0.067) and 18 days (range from 12 to 27) versus 15.5 days (range from 12 to 72) (P = 0.183) for platelet engraftment in the ETP-ALL/LBL and non-ETP ALL groups, respectively. There were no significant difference in 5-year overall survival (54.74%±10.33% vs 64.20%±10.30%, P=0.786), relapse-free survival (56.22%±10.11% vs 57.17%±12.71%, P=0.841), and cumulative incidence of relapse (30.14%±9.85% vs 22.79%±8.24%, P=0.774) between the two groups. The incidence of aGVHD (acute graft versus host disease) (P=0.922), II-IV aGVHD (P=0.940), III-IV aGVHD (P=0.664), cytomegalovirus infection (P=0.862), Epstein-Barr virus infection (P=0.610) and severe bacterial infection (P=0.145) were also similar. Conclusion: The prognosis of patients with ETP-ALL/LBL was similar to non-ETP ALL patients when they received allo-HSCT.